The judges in the democracy of the constitutional State - Rico-Chavarro, Dídima (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper is an approach to the role of judges in the democracy of the constitutional State of law, with regard to the importance between democracy and justice of judges that Zagrebelski develops as ductile democracy, inasmuch as it forwards the resolution of the difficult decisions to the weighting betweenprinciples to material justice, in order to contribute to the questioning and prohibition of the concept of the law that he considers finished in obedience to the law.